COMPARATIVE STUDY OF LABETALOL AND NIFEDIPINE IN MANAGEMENT OF HYPERTENSIVE DISORDERS OF PREGNANCY - K., HARSHITHA; PALLAVI, KOLAN (International Journal of Current Pharmaceutical Research, 2024)
Objective: The purpose of the study was to evaluate and compare effectiveness and safety of nifedipine and labetalol monotherapy in patients with hypertensive disorders of pregnancy. Methods: 100 antenatal patients were selected. Detailed obstetric history was taken and, clinical examination done and the blood pressure was checked and means arterial pressure was calculated as follows (SBP+2DBP)/3. Brachial artery blood pressure was checked with the patient in lateral recumbent position using calibrated mercury sphygmomanometer and appropriate cuff size. Korotkoff V was used to determine diastolic blood pressure. The blood pressure was monitored at 0, 6, 12, 24, 48, 72 h. The initial dosage of an antihypertensive drug and maximum dosage of the antihypertensive drug was observed. Results: In the present study, it was noted that the change in mean arterial pressure from the time of admission to 72 h were noted in the two groups which received nifedipine (132.34 vs 96.74) and labetalol (132.07 vs 93.51). There was a significant fall in the mean arterial pressure at 6 h in nifedipine group which showed statistical difference. At 48 h and 72 h fall in MAP was noted in labetalol group, which is statistically significant. The study showed that there was a sudden fall in the mean arterial pressure in nifedipine group, but labetalol had smooth and persistent fall in mean arterial pressure. It was observed in the study that fetal outcome in terms of live births (96% vs 84%) was higher in labetalol group and need for NICU admission and preterm births (18% vs 10%) was more in nifedipine group. Conclusion: The present study has shown that labetalol has got better and sustained control of hypertension in pregnancy.